Parallel Stochastic Newton Method (Journal of Computational Mathematics, 2018)
We propose a parallel stochastic Newton method (PSN) for minimizing unconstrainedsmooth convex functions. We analyze the method in the strongly convex case, and giveconditions under which acceleration can be expected when compared to its serial counterpart.We show how PSN can be applied to the large quadratic function minimization ingeneral, and empirical risk minimization problems. We demonstrate the practical efficiencyof the method through numerical experiments and models of simple matrix classes.
Keywords: optimization; parallel methods; Newton's method; stochastic algorithms.